Depressive symptoms in newly diagnosed lung carcinoma: prevalence and associated risk factors - Koya Kutty, Shahedah; How, Soon Hin; Ab Rahman, Jamalludin; Md Tahir, Mohd Faiz; Kuan, Y. C.; Ong, Choo Khoon (The Korean Academy of Tuberculosis and Respiratory Diseases, 2019)
Background: Depression is a recognized complication of lung cancer underreported in developing countries such as Malaysia. Treating and identifying depression in cancer patients increases survival and quality of life. Our objectives are to study prevalence of depressive symptoms in newly diagnosed lung carcinoma, and examine the relationship of depressive symptoms with other influencing risk factors. Methods: A 2-year, cross sectional study February 2015–February 2017, was conducted at Hospital Tengku Ampuan Afzan, and Penang General Hospital. One hundred and three patients with newly diagnosed, biopsy confirmed primary lung carcinoma were recruited. Self-rated patient’s identification sheet, validated Center for Epidemiologic Studies Depression (CES-D), and Dukes University Religion Index score from three different main languages were used. Results: Prevalence of current depressive symptoms (CES-D total score ≥16) is 37.9%. The result suggests prevalence of those at high risk of moderate to major depression, may need treatment. Multivariate analysis reveals those with good Eastern Cooperation Oncology Group factor (η2=0.24, p<0.001) married (η2=0.14, p<0.001) with intrinsic religiosity (IR) (η2=0.07, p<0.02) are more resistant to depression. Conclusion: One in three of lung carcinoma patients, are at increased risk for depression. Clinicians should be aware that risk is highest in those with poor performance status, single, and with poor IR. We suggest routine screening of depression symptoms as it is feasible, to be performed during a regular clinic visit with immediate referral to psychiatrist when indicated.